Building a trustworthy distributed fuzzing framework - Chen, Hongyu (Nanyang Technological University, 2022)
This project a is a full stack web application development project and it contains four main structures, which are frontend development, backend development, database development and distributed system management. This project is carried out by Chen Hongyu personally and under guidance from Mr. Li YueKang from Cyber Security Research Center of Nanyang Technological University.